Effect Different Levels of Calcium and Phosphorus With and Without Probiotics Inclusion on Growth Performance, Carcass Traits and Jejunum Morphology of Broiler Chickens (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This study was conducted at the poultry farm of the Department of Animal Sciences, Faculty of Agriculture, Ferdowsi University of Mashhad, for the period from 12/8/2018 to 26/9/2018. The object of this study was to evaluate the impact of the inclusion of probiotics (Pro) on growth performance, carcass traits, and jejunum morphology in broiler chickens that suffering from calcium (Ca) and available phosphorus (avP) deficiency. A total of 1440 1-d-old broilers chicks (Ross 308) were used, on the first day, birds were randomly allotted to one of the 4 treatments: (1) control diet (0.96% Ca and 0.48% avP) as recommended by the Ross 308 strain guidelines; (2) Low1 (0.864 % Ca and 0.432% avP); (3) Low2 (0.768 % Ca and 0.384% avP); and (4) Low3 (0.672 % Ca and 0.336% avP). Each treatment contained on 36 replicates and 12 chicks for each replicate except the control treatment as it contained on 12 replicates and 12 chicks for replicate. On 11 d, each treatment of low Ca and avP treatments, except control treatment, were divided into the following six groups (low1, low2 and low3 with probiotics( or (low1, low2 and low3 without probiotics). The completely randomized design was used in the experimental design. The results showed no significant differences among treatments in terms of weight gain and feed intake, while the feed conversion ratio was impacted by low-calcium and phosphorus with or without probiotics. Where the feed conversion ratio has improved in the birds fed the Low Ca and avP diets or birds fed the Low-Ca avP+Pro diets when compared with those fed the control group (P0.05). Additionally, the villus height, crypt depth and villus height to crypt depth ratio were improved in birds that fed low-calcium and phosphorus diets with Probiotics when compared with birds that fed low-calcium and phosphorus diets without probiotics. In conclusion, it is possible to decrease dietary Ca and avP levels by 10%, 20%, and 30% during the grower and finisher phases without affecting growth performance, carcass characteristics, internal organs, and intestinal morphology. Also, the addition of probiotics did not affect the traits studied above except for morphology intestinal.Research paper from the Ph.D. thesis for the first author